Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry Assay for Quantifying Fentanyl and 22 Analogs and Metabolites in Whole Blood, Urine, and Hair - Busardò, Francesco Paolo; Carlier, Jeremy; Giorgetti, Raffaele; Tagliabracci, Adriano; Pacifici, Roberta; Gottardi, Massimo; Pichini, Simona (Frontiers in Chemistry, 2019)
Recently, synthetic opioid-related overdose fatalities, led by illicitly manufactured fentanyl and analogues, increased at an alarming rate, posing a global public health threat. New synthetic fentanyl analogues have been constantly emerging onto the drug marked for the last few years, to circumvent the laws and avoid analytical detection. Analytical methods need to be regularly updated to keep up with the new trends. In this study, we aimed to develop a new method for detecting the newest fentanyl analogues with a high sensitivity, in whole blood, urine, and hair. The method is intended to provide to clinical and forensic toxicologists a tool for documenting consumption. We developed a comprehensive ultra-high-performance liquid chromatography-tandem mass spectrometry screening for quantifying fentanyl and 22 analogues and metabolites. Urine sample were simply diluted before injection; a one-step liquid-liquid extraction was performed for blood testing; and a one-step solid phase extraction was performed in hair. The chromatographic separation was short (8 min). The method was fully validated in the three matrices with a high sensitivity; limits of quantifications ranged from 2 to 6 ng/L in blood and urine, and from 11 to 21 pg/g in hair. The suitability of the method was tested with 42 postmortem blood, urine, or hair specimens from 27 fatalities in which fentanyl analogues were involved. Average blood concentrations (± SD) were 7.84 ± 7.21 and 30.0 ± 18.0 µg/L for cyclopropylfentanyl and cyclopropyl norfentanyl, respectively (n = 8), 4.08 ± 2.30 µg/L for methoxyacetylfentanyl, (n = 4), 40.2 ± 38.6 and 44.5 ± 21.1 µg/L for acetylfentanyl and acetyl norfentanyl, respectively (n = 3), 33.7 and 7.17 µg/L for fentanyl and norfentanyl, respectively (n = 1), 3.60 and 0.90 µg/L for furanylfentanyl and furanyl norfentanyl, respectively (n = 1), and 0.67 µg/L for sufentanil (n = 1); urine and hair concentrations are also reported.